Geophysical characterization of the Santa Catarina gabbro, São Sepé (RS) - Moreira, César Augusto [UNESP] (2014)
Geophysical methods are widely used in mineral exploration for several types of mineral deposits. When combined with direct studies as geochemistry, a substantial increase in the probability of ore discovery is possible in mineral exploration activities. Electrical geophysical methods are particularly promising in studies related to the search of sulphides due to the contrast of physical properties electric resistivity and chargeability. This paper presents the results obtained from the application of Resistivity (DC) and Induced Polarization methods, through the electrical profiling technique, aiming at evaluating the potential mineral of a gabbro intruded in a metasedimentary sequence, in an area where several occurrences of gold and copper were described. This gabbro is ranked on the Basic-Ultrabasic stratiform bodies, which gather peridotites, gabbros, and layered anortosites. Three radial lines of electrical profiling were performed, spaced of 60° and crossing at the area center, with readings of electric resistivity and chargeability in Wenner-Schlumberger array. The association of low resistivity and high chargeability areas has allowed defining potentially mineralized zones related to structures that condition the drainage net in the gabbro domain. Grains of gold detected through geochemical prospection of alluvial sediments dowstream from the gabbro may have originated from leaching of ores deposited in fractures through the action of river waters within the gabbro domain, possibly consisting of sulphides and gold.